X-ray differential phase-contrast imaging simulations with Geant4. (22nd October 2021) - Brombal, L; Arfelli, F; Brun, F; Longo, F; Poles, N; Rigon, L
Abstract: The development of accurate simulation tools including x-ray phase-contrast effects is of great use in the design and optimization of x-ray phase-contrast imaging (XPCI) experimental setups. When the lateral coherence of the imaging system is limited, as in most compact laboratory-based XPCI applications, phase-contrast can be effectively described through refraction effects that can be simulated with a ray-tracing approach. This work presents a practical implementation of the x-ray phase-contrast in Geant4 and validates the simulation results against theoretical predictions for the propagation-based (PB) and edge-illumination (EI) imaging configurations. The simulation includes a realistic polychromatic tungsten anode spectrum and an extended x-ray source, a virtual phantom made of plastic wires with a diameter of 1 mm, as well as an accurate description of the absorbing masks and related movement during data acquisition. Results show a good agreement between theory and simulations, with maximum discrepancies below 2% in the intensity of PB images, below 0.3 µ rad for EI refraction, and below 0.03 mm for EI projected thickness. Additionally, an often disregarded effect such as the refraction sensitivity inhomogeneity across the field of view (around 20%) was reproduced by the simulation and quantitatively explained through a theoretical model. The presented simulation platform will be extensively used for the design of a novel EI facility that is under construction at the INFN laboratories in Trieste (Italy) in the framework of the Photon-counting Edge-illumination Phase-contrast Imaging (PEPI) project.